PENGARUH PERLAKUAN ALKALI TERHADAP KEKUATAN TARIK SERAT TANDAN KOSONG KELAPA SAWIT UNTUK DIGUNAKAN PADA KOMPOSIT SERAT TKKS - Gultom, Firman; Supriadi, Harnowo; Savetlana, Shirley (FT UNILA, 2014)
Empty Palm bunches (TKKS) is one of the solid waste generated by industrial palm oil plantations which contain lots of fiber and is one of the natural fiber source that the availability of abundant in Indonesia, especially in the province of Lampung. TKKS fiber can be used as an alternative amplifier to composite materials. This research was conducted to determine the influence of the chemical composition of TKKS fiber and know the tensile strength from TKKS fiber by doing a tensile test. Alkaline treatment NaOH 5% given to fiber to separate lignin and contaminants that contained in fiber so that it can increase the tensile strength fibers. TKKS fiber is obtained processing palm oil factory by the process of boiling oil palm fresh fruit bunches with a pressure of 2.5 until 3atm at temperature 130 C during 50 – 60 minutes. TKKS already parsed and then selected and measured with a length of 6 cm and a diameter of 0.2 mm. And then given an alkaline NaOH 5%. In this research on the treatment of alkaline NaOH 5% provided that treatment during 0 hours (without treatment), 2 hour, 4 hour, 6 hour. Results from the study found that fiber tensile strength affected by the chemical composition on the fiber, the higher the tensile strength of the cellulose content is increasingly high. Tensile strength in fiber with alkali treatment 2 hours of 0,03528 Mpa, 0,3996% strain, 0,088288 MPa elasticity modulus, if compared with fiber without alkali treatment of 0,018946 MPa tensile strength, 0,2056% strain, 0,092149 MPa elasticity modulus. This is due to the levels of cellulose fibers with alkali treatment 2 hours increased by 58,2808%, if compared with fiber without alkali treatment by 13,2848%